Potassium-ion aqueous supercapattery composed by solar carbon and nickel-zinc prussian blue analogue. (October 2020) - Lobato-Peralta, Diego Ramón; Vazquez-Samperio, Juvencio; Pérez, Obed; Acevedo-Peña, Próspero; Reguera, Edilso; Cuentas-Gallegos, Ana Karina
Highlights: Relative abundant raw materials were employed to obtain double layer solar carbon and faradaic Ni-ZnHCF. Solar carbon can reach more than 215 F g −1 and exhibits excellent rate capability. Mixed Ni-ZnHCF exhibited paramount performance compare to single PBAs. Electrodes exhibit similar rate capability and energy storage capacity. Assembled K-ion supercapattery shows excellent stability evaluated by GCD and EIS. Abstract: Hybrid energy storage devices, currently known as supercapatteries, combine electrodes with two different energy storage mechanisms, double-layer and fast-kinetics faradaic processes, to deliver high specific energy at high specific power. Here, an eco-friendly synthetic route is employed to obtain negative (solar carbon) electrode, and a soft–chemistry route to synthesize positive (nickel-zinc hexacyanoferrate) electrode, to assemble a K-ion aqueous supercapattery. Activated carbon was synthesized by pyrolysis of agro-industrial waste composed by agave angustifolia leaves in a solar furnace, and mixed nickel-zinc hexacyanoferrate was prepared by simple chemical precipitation. Conventional three-electrode characterization of active materials showed that both materials exhibit similar rate capability and charge storage capacities. A supercapattery was obtained when combining these two electrodes, delivering specific energies of 9.163 W h kg −1 and 6.444 W h kg −1 at specific power values of 0.153 kW kg −1 and 5.638 kW kg −1, respectively. The assembled K-ion energy storage device retained 85% of the initial capacitance after 5000 cycles (at 2.5 Ag −1 ), with a coulombic efficiency close to 100%. Graphical abstract: Image, graphical abstract